The Synergistic Priming Effect of Exogenous Salicylic Acid and H2O2 on Chilling Tolerance Enhancement during Maize (Zea mays L.) Seed Germination - Li, Zhan; Xu, Jungui; Gao, Yue; Wang, Chun; Guo, Genyuan; Luo, Ying; Huang, Yutao; Hu, Weimin; Sheteiwy, Mohamed S.; Guan, Yajing; Hu, Jin (Frontiers in Plant Science, 2017)
Chilling stress is an important constraint for maize seedling establishment in the field. To examine the role of salicylic acid (SA) and hydrogen peroxide (H2O2) in response to chilling stress, we investigated the effects of seed priming with SA, H2O2 and SA+H2O2 combination on maize resistance under chilling stress (13°C). Priming with SA, H2O2 and especially SA+H2O2 shortened seed germination time and enhanced seed vigor and seedling growth as compared with hydropriming and non-priming treatments under low temperature. Meanwhile, SA+H2O2 priming notably increased the endogenous H2O2 and SA content, antioxidant enzymes activities and their corresponding genes ZmPAL, ZmSOD4, ZmAPX2, ZmCAT2 and ZmGR expression levels. The α-amylase activity was enhanced to mobilize starch to supply metabolites such as soluble sugar and energy for seed germination under chilling stress. In addition, the SA+H2O2 combination positively up-regulated expressions of gibberellic acid (GA) biosynthesis genes ZmGA20ox1 and ZmGA3ox2, and down-regulated GA catabolism gene ZmGA2ox1 expression; while it promoted GA signaling transduction genes expressions of ZmGID1 and ZmGID2 and decreased the level of seed germination inhibitor gene ZmRGL2. The abscisic acid (ABA) catabolism gene ZmCYP707A2 and the expressions of ZmCPK11 and ZmSnRK2.1 encoding response receptors in ABA signaling pathway were all up-regulated. These results strongly suggested that priming with SA and H2O2 synergistically promoted hormones metabolism and signal transduction, and enhanced energy supply and antioxidant enzymes activities under chilling stress, which were closely relevant with chilling injury alleviation and chilling-tolerance improvement in maize seed.